2018
DOI: 10.1007/s00264-017-3735-4
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic versus open treatment of cam-type femoro-acetabular impingement: retrospective cohort clinical study

Abstract: FAI surgery can be considered effective in improving patient symptoms. There were no differences in clinical or radiographic results between techniques. We could more accurately predict the variation ratio of NAHS after surgery than its pre-operative value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Other published series have a significant shorter FU time, but the overall time matched survival rate, and patient-reported outcomes are similar. 23,63 The overall results seem promising, but reports of more consistent outcome measures are lacking. In fact, a recent meta-analysis review on FAI surgery results 64 showed that the present literature is primarily focused on PROMs and diagnostic imaging, both reported in 93% of the included studies.…”
Section: Long-term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other published series have a significant shorter FU time, but the overall time matched survival rate, and patient-reported outcomes are similar. 23,63 The overall results seem promising, but reports of more consistent outcome measures are lacking. In fact, a recent meta-analysis review on FAI surgery results 64 showed that the present literature is primarily focused on PROMs and diagnostic imaging, both reported in 93% of the included studies.…”
Section: Long-term Resultsmentioning
confidence: 99%
“…Few studies report more than a 5-to 10-year follow-up after FAI surgery. 22,23 Thus we do not know for sure if hippreserving procedures will be cost effective and beneficial in the long term. We believe adequate patient selection, proper diagnosis based on good quality imaging, and appropriate surgery are the key factors to achieve good results in hip preservation.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed 7 studies [ 13 19 ] including 3 retrospective studies and 4 prospective cohort studies in this article. The included studies were conducted in 4 countries (Switzerland, Portugal, Brazil and USA) from 2011 to 2018, and involved 606 patients (299 patients treated with AT, 307 patients treated with OT) aged 19 to 36.12 years.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). Comparison of postoperative internal rotation angle between the 2 groups was conducted among 2 included studies, [ 13 , 17 ] which contain 94 patients (63 patients received AT and 31 patients received OT) in Figure 7 . No heterogeneity was found among studies ( P = .52, I 2 = 0%), so the fixed-effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Following a multi-criteria decision analysis, Diaz-Ledezma and Parvizi [19] concluded that a mini-open approach was preferred due to a typical association with lower costs [19]. However, Rego et al [20] in their series of 198 patients with cam FAI did not find any significant functional difference between those treated with either hip arthroscopy or open surgical hip dislocation [20]. Landsdown and colleagues [21] evaluated 707 patients who underwent surgery involving hip arthroscopy, concluding that measurement of the extent of the cam lesion was the strongest predictor of outcome following surgery [21].…”
Section: Results Of Surgery For Cam Deformitymentioning
confidence: 99%